Characterizing host-pathogen interactions between Zostera marina and Labyrinthula zosterae - Yaamini R. Venkataraman; Amanda Shore; Sukanya Dayal; James Sanghyun Lee; Mahsa Alidoost Salimi; Grace Crandall; Malina M. Loeher; Mark Stoops; Megan Swanger; Morgan E. Eisenlord; Kathryn L. Van Alstyne; Mark D. Fast; et al. (Frontiers in Marine Science, 2023)
Introduction Seagrass meadows serve as an integral component of coastal ecosystems but are declining rapidly due to numerous anthropogenic stressors including climate change. Eelgrass wasting disease, caused by opportunistic Labyrinthula spp., is an increasing concern with rising seawater temperature. To better understand the host-pathogen interaction, we paired whole organism physiological assays with dual transcriptomic analysis of the infected host and parasite. Methods Eelgrass ( Zostera marina ) shoots were placed in one of two temperature treatments, 11° C or 18° C, acclimated for 10 days, and exposed to a waterborne inoculation containing infectious Labyrinthula zosterae ( Lz ) or sterile seawater. At two- and five-days post-exposure, pathogen load, visible disease signs, whole leaf phenolic content, and both host- and pathogen- transcriptomes were characterized. Results Two days after exposure, more than 90% of plants had visible lesions and Lz DNA was detectable in 100% percent of sampled plants in the Lz exposed treatment. Concentrations of total phenolic compounds were lower after 5 days of combined exposure to warmer temperatures and Lz , but were unaffected in other treatments. Concentrations of condensed tannins were not affected by Lz or temperature, and did not change over time. Analysis of the eelgrass transcriptome revealed 540 differentially expressed genes in response to Lz exposure, but not temperature. Lz -exposed plants had gene expression patterns consistent with increased defense responses through altered regulation of phytohormone biosynthesis, stress response, and immune function pathways. Analysis of the pathogen transcriptome revealed up-regulation of genes potentially involved in breakdown of host defense, chemotaxis, phagocytosis, and metabolism. Discussion The lack of a significant temperature signal was unexpected but suggests a more pronounced physiological response to Lz infection as compared to temperature. Pre-acclimation of eelgrass plants to the temperature treatments may have contributed to the limited physiological responses to temperature. Collectively, these data characterize a widespread physiological response to pathogen attack and demonstrate the value of paired transcriptomics to understand infections in a host-pathogen system.

Contribution of cocaine-related cues to concurrent monetary choice in humans - Justin C. Strickland; Katherine R. Marks; Joshua S. Beckmann; Joshua A. Lile; Craig R. Rush; William W. Stoops (Psychopharmacology, 2018)

Separate and combined impact of acute naltrexone and alprazolam on subjective and physiological effects of oral d-amphetamine in stimulant users - Katherine R. Marks; Joshua A. Lile; William W. Stoops; Craig R. Rush (Psychopharmacology, 2014)

Reinforcing effects of modafinil: influence of dose and behavioral demands following drug administration - William W. Stoops; Joshua A. Lile; Mark T. Fillmore; Paul E. A. Glaser; Craig R. Rush (Psychopharmacology, 2005)

Social and environmental influences on opioid sensitivity in rats: importance of an opioid’s relative efficacy at the mu-receptor - Mark A. Smith; Kara A. Chisholm; Paul A. Bryant; Jennifer L. Greene; Jacob M. McClean; William W. Stoops; David L. Yancey (Psychopharmacology, 2005)

Reinforcing effects of methylphenidate: influence of dose and behavioral demands following drug administration - William W. Stoops; Joshua A. Lile; Mark T. Fillmore; Paul E. A. Glaser; Craig R. Rush (Psychopharmacology, 2005)